1, 3, 5-Tris-(4-(iso-propyl)-phenylsulfamoylmethyl)benzene as a potential Am(III) extractant: experimental and theoretical study of Sm(III) complexation and extraction and theoretical correlation with Am(III). (18th October 2018) - Morozov, Alexander N.; Govor, Evgen V.; Anagnostopoulos, Vasileios A.; Kavallieratos, Konstantinos; Mebel, Alexander M.
ABSTRACT: The problem of legacy alkaline high-level waste (HLW) both in the US and Russia, as a result of weapons production, has prompted studies of ligands for extraction of actinides, that could be possibly used in the future together with Cs extractants for combined HLW extraction processes. The tripodal trisulphonamide ligand 1, 3, 5-tris-(4-(iso-propyl)-phenylsulfamoylmethyl)benzene (4-iPr-tsa), which has pre-organised functional groups for An(III) binding was synthesised and studied for potential Sm(III) and Am(III) binding and extraction by theoretical (DFT) and experimental (extraction) methods (for Sm(III) only). Both theory and experiments suggest that even though this family of ligands shows promise for Ln(III) and An(III) binding with minima for complex formation, complexation is competing with hydrolysis, and extraction is only feasible in alkaline solutions, in the presence of high concentrations of nitrate ions. Nevertheless, up to 51.8% of Sm(III) was removed under optimal conditions (NaOH = 2 × 10 −4  M, NaNO3  = 0.1   M, [Sm]init  = 5 × 10 −5  M). Quantum chemical calculations demonstrate that the extraction of Sm(III) and Am(III) from the aqueous phase in the form of [M·(H2 O)4 ·(OH)2 ·(NO3 )] to the organic phase in the form of [M·4-iPr-tsa·(H2 O)3 ] is thermodynamically favourable. Theory also shows that Sm(III) is a reasonably good surrogate for Am(III), as the optimised structures of the Sm and Am complexes show remarkable similarities. Even though the ligand was designed with the goal of introducing favourable cation–arene interactions, along with the expected N-binding mode of the ligand in its deprotonated form, it was found that these cation–arene interactions are rather weak in this case, and coordination with O atoms of the sulphonamide, and external water molecules, is favoured instead. GRAPHICAL ABSTRACT: